A Rare Case of Extracavitary Primary Effusion Lymphoma in the Bladder and Ureter - Jiankun Tong; Sana Jadallah; William H. Rodgers; Gabriel Jung; Malvina Fulman; Abhisek Swaika (Case Reports in Hematology)
Primary effusion lymphoma (PEL) is a rare and very aggressive large B-cell lymphoma usually presenting as serous effusions without a tumor mass. It is universally associated with human herpesvirus type-8 (HHV-8) infection. It most commonly occurs in the body cavities and rarely develops as solid tumor masses in the wall of cavity and other organs, and it has been termed as extracavitary PEL. Extracavitary PEL has been reported in the lymph nodes and extranodal sites. Here we report a rare case of extracavitary PEL occurring in the bladder and ureter of a human immunodeficiency virus (HIV)-negative 76-year-old Chinese male, presenting with right leg swelling, erythema, and pain. To the best of our knowledge, this is the first case of extracavitary PEL presenting in the bladder and ureter.